Fiber Optic Introduction Workshop for Students SMK Triyadikayasa Aek Songsongan - Ruri Ashari Dalimunthe; Riki Andri Yusda; Rendy Fahrezi Ramadhan; Hariansyah Jufri (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2022)
Abstract: The community service activity entitled "Fiberoptic Introduction Workshop for Triyadikayasa Aek Songsongan Vocational School Students" aims to provide information to Triyadikayasa Aek Songsongan Vocational High School students, provide education on technological developments in the world of education. The method used in this activity is direct observation to Triyadi-kayas Aek Songsongan Vocational School by observing analyzing and introducing fiber optic technology and how to install and apply it. Optical fiber is a technology of transmission media that is being developed and is widely used to connect computer networks. In addition, information on technological developments in the introduction of optical fiber is carried out by a team of lecturers and participates in bringing students to provide technology education to the community. The end result of this service is how students of Triyadikayasa Aek Songsongan Private Vocational School can understand and install build and apply fiber optic technology which is growing rapidly and developing.Keywords: fiberoptic; network; technologyAbstrak: Fiber Optik merupakan teknologi dari media transmisi yang sedang berkembang dan banyak digunakan untuk menghubungkan jaringan komputer. Selain itu, Informasi perkembangan teknologi dalam pengenalan fiber optik dilaksanakan tim dosen dan turut serta membawa mahasiswa guna memberikan edukasi teknologi kepada masyarakat. Kegiatan ini bertujuan untuk memberikan informasi kepada siswa siswi SMK Triyadikayasa Aek Songsongan, memberikan edukasi perkembangan teknologi dalam dunia pendidikan. Metode observasi langsung ke SMK Triyadikayasa Aek Songsongan dengan melihat serta menganalisa dan memperkenalkan teknologi fiber optik serta bagaimana cara pemasangan dan pengaplikasiannya. Hasil akhir dari pengabdian ini adalah bagaimana siswa siswi SMK Swasta Triyadikayasa Aek Songsongan bisa memahami dan memasang serta membangun dan menerapkan teknologi fiber optik yang pertumbuhannya semakin pesat dan berkembang.Kata kunci: serat optik; jaringan; teknologi